Distribution of chemical elements in attic dust as reflection of their geogenic and anthropogenic sources in the vicinity of the copper mine and flotation plant - Balabanova, Biljana; Stafilov, Trajče; Sajn, Robert; Bačeva, Katerina (Springer Science and Business Media LLC, 2011)
The main aim of this article was to assess the atmospheric pollution with heavy metals due to copper mining Bučim near Radoviš, the Republic of Macedonia. The open pit and mine waste and flotation tailings are continually exposed to open air, which leads to winds carrying the fine particles into the atmosphere. Samples of attic dust were examined as historical archives of mine emissions, with the aim of elucidating the pathways of pollution. Dust was collected from the attics of 29 houses, built between 1920 and 1970. Nineteen elements (Ag, Al, As, Ba, Ca, Cd, Co, Cr, Cu, Li, Fe, K, Mg, Mn, Na, Ni, Pb, Sr, and Zn) were analyzed by atomic emission spectrometry with inductively coupled plasma. The obtained values of the investigated elements in attic dust samples were statistically processed using nonparametric and parametric analysis. Factor analysis revealed three factors governing the source of individual chemical elements. Two of them grouping Ca, Li, Mg, Mn, and Sr (Factor 1) and Co, Cr, and Ni (Factor 2) can be characterized as geogenic. The third factor grouping As, Cu, and Pb is anthropogenic and mirrors dust fallout from mining operation and from flotation tailings. Maps of areal deposition were prepared for this group of elements, from which correlation of these anthropogenic born elements was confirmed.